MSIS 2016: a comprehensive update of graduate level curriculum recommendation in Information Systems - Topi, Heikki (2016)
The process to revise MSIS 2006, the master's level curriculum recommendation for Information Systems, is getting close to completion. In spring and summer 2016, the joint AIS/ACM task force will continue the process of soliciting comments from various stakeholders, including the academic IS community and employers. The purpose of the AMCIS panel is to give the audience an update of the status of the MSIS 2016 revision process and provide the task force with feedback regarding the draft document. A significant portion of the session will be reserved for conversation. The task force is proposing significant changes to the curriculum content and structure, including the new curriculum's focus on specifying desired graduate competencies instead of articulating courses or knowledge areas/units. Some of the changes are a reflection of the changes in the process used to revise the curriculum: MSIS 2016 will be a result of a truly global process.